Cat nap - Lies, Brian (Greenwillow Books, an imprint of HarperCollinsPublishers, 2025)
In the warm, late afternoon sunlight, a girl sits on the couch reading a book. Her kitten dozes nearby. But when Kitten notices a mouse and dives after it, an epic chase through time, art, and history ensues. Is it a dream? That's up to the reader to decide, but for the kitten, every leap and bound is full of suspense and makes for a masterpiece. Caldecott Honor-winning and New York Times bestselling author-illustrator Brian Lies creates a truly unique picture book journey that invites young readers through the galleries of an art museum as well as through time, space, and history. As the cat and mouse leap from one page to the next, they are portrayed in the style of masterful artworks from history--an ancient Egyptian relief, an illuminated manuscript, a stained-glass window, a ceramic dog--each painstakingly and lovingly re-created in its original media by Brian Lies. When the sly mouse gets away, Kitten finds himself lost and alone. Will art help him find his way home?